THE ROLE OF THE CROWN PRINCE IN THE POLITICAL SYSTEM OF KUWAIT - Huwaidi, Nour (Universitas Nasional, 2021)
This paper aims to study and analyze the role of the Crown Prince in the political system of Kuwait. This paper used analytical and descriptive methods in analyzing the role of the Crown Prince in political system of Kuwait, and describing and analyzing the rules and methods and the duties related to choosing crown prince in Kuwait. The Kuwaiti constitution specified how to assume the position of crown prince, defined the duties of the crown prince, and linked the position of prime minister in the government to that of crown prince, until the position of Crown Prince was separated from the position on prime minister in 2003. The position of Crown Prince in Kuwait has played an important role since the issuance of the Kuwaiti Constitution in 1962, as the constitution specified how to assume the position of Crown Prince, the functions of the Crown Prince, and linking the position of Crown Prince to the position of Prime Minister until 2003, when the two positions were separated.